2008
DOI: 10.1080/14616730701868571
|View full text |Cite
|
Sign up to set email alerts
|

Insecurity, stress, and symptoms of psychopathology: contrasting results from self-reports versus interviews of adult attachment

Abstract: This report was designed to clarify links among self-reports of psychiatric symptomatology, stress, and adult attachment insecurity, as operationalized using measures drawn from both the developmental and social psychological literatures. Based on a sample of 160 college students, this study demonstrated that insecurity reflected in the Adult Attachment Interview (AAI) was associated with self-reports of psychiatric symptomatology principally for individuals experiencing high levels of life stress (consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
53
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 64 publications
10
53
0
5
Order By: Relevance
“…Van Dijke & Ford, 2015), which were assessed using the Dutch version of the validated 30-item Relationship Style Questionnaire (RSQ; Griffin & Bartholomew, 1994; Van Dijke, 2002). Dimensional scores (Fortuna & Roisman, 2008) were calculated for fear of abandonment (attachment-related anxiety; Cronbach’s alpha = .74) and fear of closeness (attachment-related avoidance; Cronbach’s alpha = .72).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Dijke & Ford, 2015), which were assessed using the Dutch version of the validated 30-item Relationship Style Questionnaire (RSQ; Griffin & Bartholomew, 1994; Van Dijke, 2002). Dimensional scores (Fortuna & Roisman, 2008) were calculated for fear of abandonment (attachment-related anxiety; Cronbach’s alpha = .74) and fear of closeness (attachment-related avoidance; Cronbach’s alpha = .72).…”
Section: Methodsmentioning
confidence: 99%
“…Attachment-related avoidance and anxiety were selected to represent adult relational impairment rather than the childhood-based categories of insecure attachment because they were shown to be trait-like risk factors for self-reported psychiatric symptoms (i.e. correlated with psychopathology under conditions of both high and low stress), while the insecure attachment categories were associated with psychopathology in adults only under high stress conditions (Fortuna & Roisman, 2008). …”
mentioning
confidence: 99%
“…Studies of adults' have shown that both the coherence of adults' narratives about their early attachment experiences (as assessed by the Adult Attachment Interview (Hesse, 2008;Main, Hesse, & Goldwyn, 2008), and adult attachment styles in romantic relationships (as assessed by self-report questionnaires (Brennan, Clark & Shaver, 1998)), are associated with non-optimal child-rearing experiences and psychopathology (e.g., Agrawal, Gunderson et al, 2004;Dozier, Stovall, & Albus, 1999;Fonagy, Leigh et al, 1996;Fortuna & Roisman, 2008;Fossati, Feeney et al, 2003;Meyer, Pilkonis et al, 2001;Muller, Lemieux & Sicoli, 2001;Riggs, Paulson et al, 2007;Schindler, Rainer et al, 2005;Ward, Lee & Polan, 2006). In contrast, secure attachment in childhood and adulthood is typically associated with a history of involvement in supportive and sensitive care giving relationships (Cairns, 2002;Mikulincer & Shaver, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Ward, Lee, and Pola (2006) found statistically significant positive correlations between psychopathology and dysfunctional parental attachment. Fortuna and Roisman (2008) also found positive associations between parental neglect and symptoms of depression in adulthood. Stansfeld, Head, Bartley, andFonagy (2008) retrospectively evaluated 7,279 subjects and found that a high level of parental warmth was highly correlated with decreased risk of insecure attachment styles associated with the development of psychiatric disorders in adulthood, mainly DDs.…”
Section: Introductionmentioning
confidence: 83%